Research infrastructure challenges in preparing essential biodiversity variables data products for alien invasive species. (1st February 2019) - Hardisty, Alex R; Belbin, Lee; Hobern, Donald; McGeoch, Melodie A; Pirzl, Rebecca; Williams, Kristen J; Kissling, W Daniel
Abstract: Essential biodiversity variables (EBV) are information products for assessing biodiversity change. Species populations EBVs are one class of EBVs that can be used to monitor the spread of invasive species. However, systematic, reliable, repeatable procedures to process primary data into EBVs do not yet exist, and environmental research infrastructures still must improve their capabilities to deliver EBV data products. Here, we tested the ability of two mature biodiversity data infrastructures, the Global Biodiversity Information Facility and the Atlas of Living Australia, to cooperatively produce EBV data products for three alien invasive species. We detailed workflow steps to discover, filter, retrieve and prepare the primary data before evaluating species' distributional changes. The two data infrastructures were able to execute several workflow steps, but external tools, third-party sources and expert judgement were required, and a repeatable workflow was difficult to establish. Nevertheless, the resulting data products revealed strong range expansions for the invasive species, demonstrating the policy-relevant information about global environmental change that can be provided by EBV data products. Our results show that more coordination between infrastructure providers is needed to efficiently produce EBV-ready data products for invasion monitoring in a repeatable fashion. Addressing these issues will allow improved tracking of invasive species range dynamics and hence monitoring of ongoing global biodiversity change.